Subtotal cor triatriatum sinister associated with bilateral partial anomalous pulmonary venous return - Onur Işık; Muhammet Akyuz; Mehmet Fatih Ayık; Yuksel Atay (KARE Publishing, 2016)
Cor triatriatum sinister is a rare congenital cardiac pathology, representing only 0.1% of congenital cardiac anomalies, and often associated with other cardiac defects. In classic cor triatriatum sinister, the pulmonary venous chamber receives all pulmonary veins and drains into the left atrium through a variable-sized orifice. The case of a 4-month-old male patient who had subtotal cor triatriatum sinister associated with right and left upper anomalous pulmonary venous return is presented.